Models of economic growth (London : Macmillan, 1973)
This book comprise of proceedings of a Conference held by the International Economic Association at Jerusalem. It covers growth, growth and technology; capital and developing economies.
lje 19/10/18
Loans
Keywords: Economic growth; Economic development; Developing economies